Shaping intercultural communication through the French language - Umarova , Obidaxon (The Lingua Spectrum, 2025)
This article explores the role of the French language in shaping intercultural communication. The theoretical foundations of intercultural interaction are analyzed from a linguistic and socio-cultural perspective. Particular attention is given to Edward Hall’s high- and low-context culture theory, Geert Hofstede’s cultural dimensions, Michael Byram’s model of intercultural communicative competence (ICC), and Lev Vygotsky’s socio-cultural theory. The article examines the role of the French language as a means of intercultural communication in diplomacy and education, as well as the process of language acquisition within the diverse francophone world. Additionally, the limitations of classical theories in fully capturing the multifaceted cultural characteristics of francophone communities are discussed. In conclusion, the study highlights the necessity of understanding not only linguistic aspects but also cultural codes for effective intercultural communication.